Identification of Epstein-Barr virus proteins as putative targets of the immune response in multiple sclerosis - Sabine Cepok; Dun Zhou; Ruchi Srivastava; Stefan Nessler; Susanne Stei; Konrad Büssow; Norbert Sommer; Bernhard Hemmer (2005)
MS is a chronic inflammatory and demyelinating disease of the CNS with as yet unknown etiology. A hallmark of this disease is the occurrence of oligoclonal IgG antibodies in the cerebrospinal fluid (CSF). To assess the specificity of these antibodies, we screened protein expression arrays containing 37,000 tagged proteins. The 2 most frequent MS-specific reactivities were further mapped to identify the underlying high-affinity epitopes. In both cases, we identified peptide sequences derived from EBV proteins expressed in latently infected cells. Immunoreactivities to these EBV proteins, BRRF2 and EBNA-1, were significantly higher in the serum and CSF of MS patients than in those of control donors. Oligoclonal CSF IgG from MS patients specifically bound both EBV proteins. Also, CD8+ T cell responses to latent EBV proteins were higher in MS patients than in controls. In summary, these findings demonstrate an increased immune response to EBV in MS patients, which suggests that the virus plays an important role in the pathogenesis of disease.